Education to raise community awareness in preventing forest and peatland fires - Ajeng Candra Indrawati; Muhardi Muhardi; Oktaviana Tantri; Muhamad Fajar Irawan; Indra Sanjaya Purba; Oktavia Wulandari; Tia Amanda; Muhammad Ghaza Eka Putra (Universitas Muhammadiyah Magelang, 2023)
Forest and peatland fires in Jangkang Dua Village, Kubu Raya Regency, pose a recurring issue, transpiring nearly every year. Over the past three years, there have been forest and peatland fires covering an estimated area of approximately 6 hectares. This predicament can lead to various adverse impacts, such as ecological damage, health disturbances, and economic setbacks for the community. Hence, there is a need to enhance the vigilance of the Fire Care Community to preempt future fires. This program is scheduled for implementation from June to December 2022. The approach involves educational activities focusing on forest and peatland fire disaster mitigation, restoration of burnt peatlands, canalization, and peatland vegetation. Additionally, firefighting equipment has undergone renovation. Evaluation results indicate the program's considerable success, achieving a percentage index of 90.88%. Findings from this service activity affirm that PPK Ormawa activities are effective in heightening the Fire Concern Community's alertness.